الأنماط الشخصية للمدراء و دورها في تحديد الاستراتيجيات التسويقية : دراسة استطلاعية في الشركة العامة للأدوية و المستلزمات الطبية/نينوى - ليلى جارالله خليل; مارب حازم عبدالرزاق (PROSPECTIVE RESEARCHES, 2023)
The research Deals with the role of managers’ personality Styles in marketing strategies determination in the State Company for drugs and medical requirements in nenava city. The research's problem is to determine the relation between personal patterns and marketing strategies. The research aim's at testing the relationship and the effect between the independent variable (personal patterns), and dependent variable (marketing strategies). We derived few hypotheses to display the correlations and effects between research variables. We selected a sample which consists of (50) managers and managerial unit authorities, and we used questionnaire to obtain the information, In addition to many statistical method of data analysis. This research reached a group of conclusions; one of those conclusions is that the personal patterns of managers have a role in determinimg the marketing strategy. Eventually we presented group of recommendations to improve the organization.